2009
DOI: 10.1677/erc-08-0224
|View full text |Cite
|
Sign up to set email alerts
|

Expression of excision repair cross complementing group 1 and prognosis in adrenocortical carcinoma patients treated with platinum-based chemotherapy

Abstract: Therapeutic progress in adrenocortical carcinoma (ACC) is severely hampered by its low incidence. Platinum-based chemotherapies are the most effective cytotoxic treatment regimens in ACC but response rates remain !50%. In other tumor entities, expression of excision repair cross complementing group 1 (ERCC1) predicts resistance to platinum compounds. Therefore, we correlated ERCC1 protein expression and clinical outcome. We have retrolectively established adrenal tissue microarrays and analyzed prospectively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…22 No particular signature for response to IGF-1R inhibition has yet been identified in ACC. A possible negative impact on response to platinum-based therapies has been found for high expression levels of the DNA repair gene excision repair complementation group 1 (ERCC1), 23 and high ribonucleotide reductase large subunit (RRM1) gene expression had some association with poor efficacy of adjuvant mitotane therapy. 24 As expected, the pharmacokinetic profile of linsitinib was similar to that observed in a dosedetermining phase 1 study, with rapid absorption after oral dose and accumulation following continuous twice-daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…22 No particular signature for response to IGF-1R inhibition has yet been identified in ACC. A possible negative impact on response to platinum-based therapies has been found for high expression levels of the DNA repair gene excision repair complementation group 1 (ERCC1), 23 and high ribonucleotide reductase large subunit (RRM1) gene expression had some association with poor efficacy of adjuvant mitotane therapy. 24 As expected, the pharmacokinetic profile of linsitinib was similar to that observed in a dosedetermining phase 1 study, with rapid absorption after oral dose and accumulation following continuous twice-daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…As a possible mechanism, Germano et al (2015) showed that the RRM1 gene interferes with mitotane metabolism in ACC cells. Ronchi et al (2009) investigated protein expression of excision repair cross complementing group 1 (ERCC1) as a predictor for response to platinum-based chemotherapy in patients with ACC. High ERCC1 expression was correlated with a worse overall survival in patients treated with platinum-based chemotherapy.…”
Section: Prognostic and Predictive Markersmentioning
confidence: 99%
“…[35][36][37] Briefly, hematoxylin and eosin-stained sections of formalin-fixed and paraffin-embedded tissue blocks were evaluated to identify representative areas of well-preserved morphology. The corresponding area on the paraffin block was marked for tissue punching.…”
Section: Tissue Microarrays (Tmas)mentioning
confidence: 99%